Evaluating Sheath Blight Resistance in Rice Using Detached Tiller and Field Screening Method - Chaudhary, Bedanand (Journal of Nepal Agricultural Research Council, 2016)
In present study physical resistance test on 12 rice varieties against sheath blight (ShB) caused by Rhizoctonia solani was examined. A detached tiller test was used to measure components of ShB physiological resistance at Regional Agricultural Research Station (RARS), Tarahara, Nepal. The varieties were evaluated in a randomized complete block design (RCBD) with 3 replications in year 2010-12. A sclerotium was inserted below the leaf collar of individual tillers maintained in tubes filled with water. Only the 56-day old susceptible plants were inoculated. After 7 days of inoculation, number of lesions, dead leaves, vertical sheath colonization and disease severity were measured. In 2011, field experiments were conducted with three replications to address morphological resistance in 28 rice genotypes. Disease incidence was recorded on 14, 21 and 28 days after inoculation. The number of dead leaves differed only numerically while disease variables significantly (P=0.004) varied among varieties. The other variables were highly correlated with each other. Cluster analysis of variables formed three varietal groups; Sabitri with lowest, and Jasmine-85 and Betichikon having highest values. Rice genotypes differed significantly (P=0.05) for disease incidence and area Under Disease Progress Curve (AUDPC). Tetep and IAC-165 had the lowest and highest terminal disease incidences and AUDPC, respectively. Sabitri, MTU-1010 and IR-26 recorded lower AUDPC values. Hence, Tetep and Sabitri could be used as donors in hybridization and their plant morphology could be considered as selection guide for improving ShB resistance in rice. Journal of Nepal Agricultural Research Council Vol.1 2015 pp.1-8